1991
DOI: 10.1177/000841749105800303
|View full text |Cite
|
Sign up to set email alerts
|

Reality Orientation Thirty Years Later: Are We Still Confused?

Abstract: Reality Orientation (RO) inte rvention represents the first significant attempt at rehabilitation programming for the disoriented, institutionalized elderly. Early anecdotal accounts reported sweeping positive effects. A first sign of hope for this severely disabled population, RO rapidly became widely implemented and continues to be a commonly accepted approach by numerous disciplines. However, careful examination of the research and clinical practice literature reveals many difficulties with the conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Reality orientation fails to provide a strong theoretical rationale for why it works (Bowlby, 1991). Reality orientation fails to provide a strong theoretical rationale for why it works (Bowlby, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Reality orientation fails to provide a strong theoretical rationale for why it works (Bowlby, 1991). Reality orientation fails to provide a strong theoretical rationale for why it works (Bowlby, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…One of the first psychological therapies that drew on person-centered approaches for dementia patients was reality orientation therapy (Bowlby, 1991; Spector et al, 2000), which involves repeating orienting information, such as the date or the weather, over a prolonged period of time each day (Wallis et al, 1983). This approach aims to re-orient patients with dementia to their environments and to increase their engagement (Bowlby, 1991). The literature contends that reality orientation therapy should occur within a person-centered framework in which care providers facilitate positive, quality interactions with patients rather than simply providing information (Dietch et al, 1989).…”
Section: Non-pharmacological Treatment Approachesmentioning
confidence: 99%
“…RCTs utilizing reality orientation therapy have demonstrated mild, short-term cognitive improvements; however, they have not shown that it elicits a significant reduction in overall BPSD (Hanley et al, 1981; Wallis et al, 1983; Baldelli et al, 1993; Onder et al, 2005). Unfortunately, one frequent method of delivering reality orientation therapy utilizes a classroom approach (Bowlby, 1991), but patients who exhibit aggressive symptoms or wandering are often excluded due to concerns about managing disruptions in a classroom setting (O’Connell et al, 2007). Consequently, no studies have specifically examined the effects of reality orientation therapy on behaviors within the HIDA domain.…”
Section: Non-pharmacological Treatment Approachesmentioning
confidence: 99%
“…The practice of intervention programmes for persons with dementia was the most common practice. Such interventions included reality orientation (Holden & Woods, 1982;Bowlby, 1991); life review or reminiscence (Kiernat, 1979); purposeful activities and occupations (Baum, 1995;Borell, Gustavsson, Sandman & Kielhofner, 1994;Burton, 1980); music therapy (Casby & Holm, 1994); sensory integration (Robichaud, Hebert & Desrosiers, 1994); and environmental modifications (Gitlin & Corcoran, 1993). Most of the studies examined the effectiveness of a treatment intervention in enhancing the functional performance or reducing disturbing behaviours of persons with dementia.…”
Section: Dementia and Occupational Therapy Practicementioning
confidence: 99%